Tafsir, Ta’wil Hingga Tarjamah Sebagai Instrumen Penting dalam Menginterpretasikan Ayat-Ayat Al-Qur’an - Hakmi Hidayat; Fadel Muhammad Muhtadillah; Mochammad Wildan Qolbi Habibi; M. Yasin Yusuf (CV. ITTC INDONESIA, 2024)
The Al-Qur'an is a word or revelation from Allah using Arabic to be dedicated specifically to the Prophet Muhammad SAW in fluent Arabic, which contains the main points of Islamic law. The purpose of this writing is to provide understanding and breadth in interpreting the revelation of Allah in the form of holy verses from the Koran according to the portions and forms desired. Where the Al-Qur'an is also proof of prophethood and a guide for mankind. To understand every point and aspect of the meanings of the Al-Qur'an requires knowledge that is clearly able to interpret the intent and meaning of the verses of the Al-Qur'an. So that humans can carry out actions according to Allah’s instructions. The verses in the Qur'an are kalamullah which contain extensive lessons for those who read and hear them. Arabic, which is so complex and has a wide meaning, needs to be studied in order to understand the Qur'an. So, after the death of the Prophet Muhammad, the science that explains the application and meaning of the verses of the Qur'an began to be made into a concrete study of knowledge and was divided into three, namely Tafsir, Ta'wil and Tarjamah.